COVID-19 Pandemic and Maternal Psychological Wellbeing During the Malaysian Movement Control Order: A Cross-Sectional Study - Kalok, Aida; Syed Anwar Aly, Syarifah Aminah; Abdul Rahman, Rahana; Mahdy, Zaleha Abdullah; Sharip, Shalisah (Frontiers in Psychiatry, 2022)
Background: COVID-19 pandemic had resulted in nationwide lockdown as a disease control measure. Potential harm to self and baby due to COVID-19 infection as well as uncertainties about delivery are among contributors to maternal anxiety. We aimed to assess the prevalence of psychological distress among pregnant women during the Malaysian Movement Control Order (MCO). Methods: A cross-sectional study was conducted between May and June 2020 in a teaching hospital in Kuala Lumpur, Malaysia. A self-administered electronic questionnaire was distributed which included the following; (1) Depression, Anxiety and Stress Scale-21 (DASS 21), (2) Short Warwick Edinburgh Mental Wellbeing Scale (SWEMWBS), (3) MCO effect questionnaire, and (4) newly designed COVID-19 pregnancy-related anxiety. Chi-square test and logistic regression were performed to determine significant associations whilst mean scores comparison were conducted through Mann-Whitney-U-test. Results: Four hundred and fifteen women were included in the final analysis. The prevalence of psychological distress among our cohort was 14.7%; with a two-fold increase of risk among the non-Malays (AOR 1.98, 95% CI 1.00–3.89) whilst a greater number of social support showed a protective effect (AOR 0.51, 95%CI 0.28–0.92). Malay ethnicity (p < 0.001) alongside greater household income (p = 0.014) were positive predictors of a higher sense of maternal wellbeing. Multiparous women and those of higher economic status experienced the more negative effect of the MCO. Around 88% of our women reported a higher level of COVID-19 pregnancy-related anxiety. Younger (p = 0.017) and first-time mothers (p = 0.039) were more likely to be anxious. Although adequate maternal knowledge on COVID-19 was associated with a greater sense of maternal wellbeing (p = 0.028), it was also linked to a higher level of COVID-19 related anxiety (AOR 3.54, 95% 1.29–9.70). Conclusion: There was a relatively low prevalence of psychological distress among expectant mothers in Malaysia during the first wave of the COVID-19 pandemic. Expectant mothers should receive accurate and reliable information on the effect of COVID-19 on pregnancy to relieve some maternal anxiety. Maternal health screening is important to identify individuals who would benefit from extra support and mental health intervention, especially in prolonged lockdown.